Outcomes and Complications After Primary Arthroscopic Suprapectoral Versus Open Subpectoral Biceps Tenodesis for Superior Labral Anterior-Posterior Tears or Biceps Abnormalities: A Systematic Review and Meta-analysis. Issue 8 (28th August 2020) - Deng, Zi Jun; Yin, Clark; Cusano, Joseph; Abdul-Rassoul, Hussein; Curry, Emily J.; Novikov, David; Ma, Richard; Li, Xinning
Background: Biceps tenodesis is a surgical treatment for both superior labral anterior-posterior (SLAP) tears and long head of the biceps tendon (LHBT) abnormalities. Biceps tenodesis can be performed either above or below the pectoralis major tendon with arthroscopic or open techniques. Purpose: To analyze the outcomes and complications comparing primary arthroscopic suprapectoral versus open subpectoral biceps tenodesis for either SLAP tears or LHBT disorders. Study Design: Systematic review; Level of evidence, 4. Methods: A search strategy based on the PRISMA (Preferred Reporting Items for Systematic Meta-Analyses) protocol was used to include 18 articles (471 patients) from a total of 974 articles identified. Overall exclusion criteria included the following: non–English language, non–full text, biceps tenodesis with concomitant rotator cuff repair, review articles, meta-analyses, and case reports. Data were extracted and analyzed according to procedure type and tenodesis location: arthroscopic suprapectoral biceps tenodesis (295 patients) versus open subpectoral bicepts tenodesis (176 patients). Results: For arthroscopic suprapectoral biceps tenodesis, the weighted mean American Shoulder and Elbow Surgeons (ASES) score was 90.0 (97 patients) and the weighted mean Constant score was 88.7 (108 patients); for open subpectoral biceps tenodesis, the mean ASES score was 91.1 (199 patients) and mean Constant score was 84.7 (65 patients). Among the 176 patients who underwent arthroscopic biceps tenodesis, there was an overall complication rate of 9.1%. Among the 295 patients who underwent open biceps tenodesis, there was an overall complication rate of 13.5%. Both residual pain (5.7% vs 4.7%, respectively) and Popeye deformity (1.7% vs 1.0%, respectively) rates were similar between the groups. Open subpectoral biceps tenodesis had higher reoperation (3.0% vs 0.0%, respectively), wound complication (1.0% vs 0.0%, respectively), and nerve injury (0.7% vs 0.0%, respectively) rates postoperatively. A meta-analysis of 3 studies demonstrated that both methods had similar ASES scores ( P = .36) as well as all-cause complication rates (odds ratio, 0.76 [95% CI, 0.13-4.48]; P = .26). Conclusion: Patients undergoing arthroscopic suprapectoral biceps tenodesis for either SLAP tears or LHBT abnormalities had similar outcome scores and complication rates compared with those undergoing open subpectoral biceps tenodesis. Additionally, both residual pain and Popeye deformity rates were similar between the 2 groups.